Incorporation and survival of probiotic bacteria in whey cheese matrices - Madureira, Ana R. (2011)
The viabilities of probiotic strains of Lactobacillus acidophilus, Lactobacillus paracasei, Bifidobacterium animalis, and Lactobacillus brevis were studied following incorporation in a whey cheese matrix. Experimental production of plain, as well as sugar-added or salt-added whey cheeses, was based on the traditional manufacture protocol of Requeijäo, a Portuguese whey cheese that essentially results from protein denaturation via heating of whey at about 85°C. After inoculation, the experimental whey cheeses were incubated at 7°C for 28 d. Our results have shown that all strains considered were able to maintain (or even increase) their initial viable numbers; L. paracasei ssp. paracasei strain LCS-1 and L. acidophilus strain Ki exhibited the highest cell viability in plain Requeijão by the end of the storage period—an increase of ca. 2 log cycles in their viable numbers was actually recorded. Among the parameters studied, bacterial species and matrix nature had the most important effect upon viable counts, whereas time of storage was the least important.